Analisis Kecurangan Laporan Keuangan dengan Pendekatan Fraud Hexagon pada Badan Usaha Milik Negara yang Terdaftar di Bursa Efek Indonesia - Danar Irianto; Desrahayu Vinarsinta Uli Munthe; Ridho Tanso Rikalmi (Pusat P2M Politeknik Negeri Batam, 2025)
This study aims to analyze various factors from the fraud hexagon in relation to detecting financial statement fraud in State-Owned Enterprises listed on the Indonesia Stock Exchange (IDX) during the 2019–2021 period. The study population consists of 24 State-Owned Enterprises listed on the IDX. A purpos- ive sampling method was used to select the sample, resulting in 13 State-Owned Enterprises that met the research criteria, with a total of 39 observations. The novelty of this research lies in the addition of a new variable financial stability as an indicator to measure stimulus or pressure. The data were processed using lo- gistic regression analysis with IBM SPSS version 27. The findings indicate that Rationalization, proxied by Total Accruals, has a significant positive effect on detecting financial statement fraud. In contrast, financial stability, external pres- sure, financial targets, opportunity, capability, arrogance, and collusion do not show significant effects on the detection of financial statement fraud.